On the Scottish Book Problem 155 by Mazur and Sternbach - Mori, Michiya (Comptes Rendus. Mathématique)
Problem 155 of the Scottish Book asks whether every bijection $U\colon X→ Y$ between two Banach spaces $X, Y$ with the property that, each point of $X$ has a neighborhood on which $U$ is isometric, is globally isometric on $X$. We prove that this is true under the additional assumption that $X$ is separable and the weaker assumption of surjectivity instead of bijectivity.